Depositional environment, hydrocarbon generation and expulsion potential of the middle Permian Pingdiquan source rocks based on geochemical analyses in the eastern Junggar Basin, NW China. Issue 4 (19th May 2017) - Bai, H.; Pang, X.; Kuang, L.; Wan, Z.; Pang, H.; Wang, X.; Jia, X.; Song, X.
ABSTRACT: As the most important source rocks in the eastern Junggar Basin, the middle Permian Pingdiquan (P2 p) source rocks have attracted increasing attention after the discovery of tight oil in the Shazhang uplift. The P2 p source rocks are widely distributed (up to 7546 km 2 ) and have an elevated thickness in the eastern Junggar Basin. To explore the P2 p tight oil resource in the eastern Junggar Basin, 113 core samples from 34 exploration wells were analysed geochemically and re-examined for their organic matter abundance, type and thermal maturity, hydrocarbon potential and sedimentary environment. Geochemical analysis results indicate that the P2 p source rocks are fair to good source rocks dominated by Type II kerogen, presently in a low mature–mature stage, and biomarkers and trace elements indicate deposition in a terrestrial to coastal environment under oxic to dysoxic, and fresh to brackish conditions, with possible intermittent seawater influence, implying proximity to the open sea. Based on hydrocarbon expulsion modelling, hydrocarbon expulsion began at 0.87% R o, and the peak expulsion occurred at 1.1% R o . Hydrocarbon generation intensities in the Shazhang uplift and the Wucaiwan sag are relatively large, with values centred at 4–6.5 million t/km 2 and 4–6 million t/km 2, respectively, with total hydrocarbon generation and expulsion from the P2 p source rocks approximately 4.56 × 10 9 t and 1.44 × 10 9 t, respectively, indicating significant tight oil exploration potential in the eastern Junggar Basin. The Shazhang uplift and the Wucaiwan sag are two hydrocarbon expulsion centres in the study area with the largest hydrocarbon expulsion intensity centred around the Shazhang uplift, exceeding 3 × 10 6 t/km 2 . We suggest that the area with high hydrocarbon expulsion intensities is a favourable target for tight oil accumulation and exploration.